Stable near‐surface ocean salinity stratifications due to evaporation observed during STRASSE. Issue 5 (30th May 2014) - Asher, William E.; Jessup, Andrew T.; Clark, Dan
Abstract Under conditions with a large solar flux and low wind speed, a stably stratified warm layer forms at the ocean surface. Evaporation can then lead to an increase in salinity in the warm layer. A large temperature gradient will decrease density enough to counter the density increase caused by the salinity increase, forming a stable positive salinity anomaly at the surface. If these positive salinity anomalies are large in terms of the change in salinity from surface to the base of the gradient, if their areal coverage is a significant fraction of the satellite footprint, and if they persist long enough to be in the satellite field of view, they could be relevant for calibration and validation of L‐band microwave salinity measurements. A towed, surface‐following profiler was deployed from the N/O Thalassa during the Subtropical Atlantic Surface Salinity Experiment (STRASSE). The profiler measured temperature and conductivity in the surface ocean at depths of 10, 50, and 100 cm. The measurements show that positive salinity anomalies are common at the ocean surface for wind speeds less than 4 m s−1 when the average daily insolation is >300 W m−2 and the sea‐to‐air latent heat flux is greater than zero. A semiempirical model predicts the observed dependence of measured anomalies on environmental conditions. However, the model results and the field data suggest that these ocean surface salinity anomalies are not large enough in terms of the salinity difference to significantly affect microwave radiometric measurements of salinity.